2016
DOI: 10.3390/molecules21030382
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Astaxanthin from Litopenaeus Vannamei on Carrageenan-Induced Edema and Pain Behavior in Mice

Abstract: Carrageenan produces both inflammation and pain when injected in mouse paws via enhancement of reactive oxygen species formation. We have investigated an effect of astaxanthin extracted from Litopenaeus vannamei in carrageenan-induced mice paw edema and pain. The current study demonstrates interesting effects from astaxanthin treatment in mice: an inhibition of paw edema induced in hind paw, an increase in mechanical paw withdrawal threshold and thermal paw withdrawal latency, and a reduction in the amount of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 66 publications
9
19
0
1
Order By: Relevance
“…In another study, it was shown that AST at the dose of 5 mg/kg, i.p, reduces von Frey mechanical hyperalgesia and at higher doses, 10 mg/kg, i.p., reduces both thermal and mechanical hypersensitivity in rats undergoing chronic constriction of the sciatic nerve via oxido‐inflammatory and NMDA receptor down‐regulation pathway (Sharma et al., ). In a model of carrageenan‐induced inflammatory pain, AST also indicates an efficacy comparable to indomethacin in relieving mechanical and thermal hyperalgesia (Kuedo, Sangsuriyawong, Klaypradit, Tipmanee, & Chonpathompikunlert, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, it was shown that AST at the dose of 5 mg/kg, i.p, reduces von Frey mechanical hyperalgesia and at higher doses, 10 mg/kg, i.p., reduces both thermal and mechanical hypersensitivity in rats undergoing chronic constriction of the sciatic nerve via oxido‐inflammatory and NMDA receptor down‐regulation pathway (Sharma et al., ). In a model of carrageenan‐induced inflammatory pain, AST also indicates an efficacy comparable to indomethacin in relieving mechanical and thermal hyperalgesia (Kuedo, Sangsuriyawong, Klaypradit, Tipmanee, & Chonpathompikunlert, ).…”
Section: Discussionmentioning
confidence: 99%
“…One-way analysis of variance with Tukey post-hoc test was used. SCI, Spinal cord injury; AST, Astaxanthin (10 μl of 0.2 mM, intrathecal, 30 min post-injury); DMSO, dimethylsulfoxide thermal hyperalgesia (Kuedo, Sangsuriyawong, Klaypradit, Tipmanee, & Chonpathompikunlert, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the supplementation of astaxanthin and vitamin E in feed accelerate the gonad maturity in the shrimp broodstock. It is due to astaxanthin alleviate PGE2 (prostaglandin) hormone when the shrimp reaches the final gonad maturity (Kuedo et al, 2016). Therefore, the decrease of PGE2 (prostaglandin) hormones leads gonads to develop properly and the quality of eggs remain good due to lack of egg decay.…”
Section: Discussionmentioning
confidence: 99%
“…Carrageenan-induced paw edema in rats is one of the experimental animal model for exploring anti-inflammatory potential of extracts and other compounds [17]. Subcutaneous injection of carrageenan in the hind paw of rats induced local edema.…”
Section: Discussionmentioning
confidence: 99%